Why Are Spatial Skill and Mathematics Related?. (18th April 2019) - Mix, Kelly S.
Abstract: Research has demonstrated strong relations between spatial skill and mathematics across ages and in both typical and atypical populations, suggesting that a significant proportion of variance in mathematics performance can be explained by variance in spatial skill. Why do these relations exist and how do they develop? Studies of dimensionality in the two domains suggest the relation holds across tasks and is not limited to specific spatial or mathematics subskills. Spatial skills might perform several functions in real‐time problem solving, but these have not been differentiated empirically. The relation appears to be based on automatic shared processing, as well as strategic recruitment of spatial processes. Developmentally, the relation is consistent in its strength, but may change qualitatively, particularly in response to novel mathematics content.